2019
DOI: 10.7759/cureus.4407
|View full text |Cite
|
Sign up to set email alerts
|

Visual Presentation and Factors Affecting Visual Outcome in Children with Craniopharyngioma in East Coast States of Peninsular Malaysia: A Five-year Review

Abstract: Purpose To describe the visual presentation and factors affecting visual outcome in pediatric patients treated for craniopharyngioma at a referral center in the East Coast states of Peninsular Malaysia. Methodology A retrospective review of medical records of children aged 17 years and below who had been treated for craniopharyngioma in Hospital Universiti Sains Malaysia from January 2014 to December 2018. The data collected included age, gender, presenting symptoms and duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…� Cohort drawn from the same community as the exposed cohort • Cohort drawn from a different source • No description of the derivation of the non-exposed cohort PLOS ONE https://doi.org/10.1371/journal.pone.0240016.g001 [27,[79][80][81], Israel [82][83][84][85] and Japan [19,[86][87][88]; 3 studies in Canada [10,25,89], Italy [90][91][92] and The Netherlands [93][94][95]; 2 studies in Australia [6,96], Korea [97,98], Saudi Arabia [99,100], Turkey [32,101]; 1 study in Bulgaria [102], Denmark [103], Iran [104], Lithuania [105], Malaysia [7], Romania [106], Spain [107] and Taiwan [108]; and for 1 study the country was not reported [109]. With regard to the included children with CP, 1236 were females and the mean age ranged from 0 [39,93] All studies had a retrospective study design, of which 5 studies also had a prospective follow up [14,25,70,…”
Section: Domains Predefined Criteria Maximum Number Of Stars Per Domainmentioning
confidence: 99%
See 4 more Smart Citations
“…� Cohort drawn from the same community as the exposed cohort • Cohort drawn from a different source • No description of the derivation of the non-exposed cohort PLOS ONE https://doi.org/10.1371/journal.pone.0240016.g001 [27,[79][80][81], Israel [82][83][84][85] and Japan [19,[86][87][88]; 3 studies in Canada [10,25,89], Italy [90][91][92] and The Netherlands [93][94][95]; 2 studies in Australia [6,96], Korea [97,98], Saudi Arabia [99,100], Turkey [32,101]; 1 study in Bulgaria [102], Denmark [103], Iran [104], Lithuania [105], Malaysia [7], Romania [106], Spain [107] and Taiwan [108]; and for 1 study the country was not reported [109]. With regard to the included children with CP, 1236 were females and the mean age ranged from 0 [39,93] All studies had a retrospective study design, of which 5 studies also had a prospective follow up [14,25,70,…”
Section: Domains Predefined Criteria Maximum Number Of Stars Per Domainmentioning
confidence: 99%
“…In the majority of studies, visual function in children with CP at diagnosis was not a primary outcome measure, but details about visual function at diagnosis could be obtained from tables containing baseline characteristics. Precisely 10 studies reported primarily visual function and/or long term visual ouctomes in children with CP [6,7,10,39,52,53,72,83,102,107]. Table 4 shows the results of the risk of bias assessment by the Newcastle-Ottawa Scale (NOS) for the included studies.…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations